Original articleIncreased nitric oxide levels in cerebellum of cachectic rats with Walker 256 solid tumor - Fenner, Fabio Leandro; Guarnier, Flavia Alessandra; Bernardes, Sara Santos; Ramalho, Leandra Naira Zambelli; Cecchini, Rubens; Cecchini, Alessandra Lourenço (Folia Neuropathologica, 2015)
In cancer cachexia, the role of nitric oxide (NO) in the central nervous system remains unclear. Cerebellar degeneration has been reported in cancer patients, but the participation of NO has not been studied. Thus, this study investigated the mechanism of oxidative cerebellar injury in a time-course cancer cachexia experimental model. The cachexia index is progressive and evident during the evolution of the tumor. Nitric oxide and lipid hydroperoxidation quantification was performed using a very sensitive and precise chemiluminescence method, which showed that both analyzed parameters were increased after tumor implantation. In the day 5 group, NO was significantly increased, and this experimental time was chosen to treat the rats with the NO inhibitors N-nitro-L-arginine methyl ester (L-NAME) and aminoguanidine (AG). When treated with NO inhibitors, a significant decrease in both NO and lipid hydroperoxide levels occurred in the cerebellum. 3-nitrotyrosine was also analyzed in cerebellar tissue by immunohistochemistry; it was increased at the three experimental time points studied, and decreased when treated with L-NAME and AG. Besides demonstrating that lipid hydroperoxidation in the cerebellum of rats with cachexia increases in a time-dependent manner, this study is the first to describe the participation of NO and its oxidized product 3-NT in the cerebellum of cachectic rats bearing the Walker 256 solid tumor.